Harmonia in commercio vs Harmonia absque commercio. Kant’s eclectical dealing with causality. - Lorini, Gualtiero (Con-Textos Kantianos. International Journal of Philosophy, 2015)
The present paper aims to provide an overview on Kant’s dealing with the main theories of causality which were proposed and discussed in his time. The goal is to show that, since the pre-critical period, he has never simply accepted the theories of causality that he could find in second-scholastic sources, but has always tried to develop an original position. Starting from a general acceptance of the theory of the “physical influx”, Kant tries to amend this theory, as it had been roughly provided by Knutzen and Crusius. This emendation is carried out through elements coming from the Leibnitian tradition. But neither in this field Kant totally embraces the Wolffian, as well as the Baumgartenian model. The paper tries also to shed light on the way in which the critical conception of space allows Kant to fulfill his original theory of causality as an amended version of the physical influx.
Keywords: Physical Influx; Occasionalism; Pre-established Harmony; Causality; Space